Modification of semantics of social terms of the modern Chinese language - Saodat Abdullayevna, Nasirova (Opción, 2019)
The article aims to investigate modification of semantics of social and political terms of the modern Chinese language in political discourse via comparative research methods. As a result, the successes of China in the field of international cultural and humanitarian cooperation, scientists associated with the implementation of the concept of soft power. In conclusion, along with the semasiological analysis of the terms 软实力soft power and 文化外交 cultural diplomacy, the analysis of the semantic field of the terms 改革reform, 普遍繁荣 general prosperity, 透明度 openness is also affected